Measurement Of Job Satification: Transformational Leadership And Interpersonal Communication Impact On Work Discipline - Mochammad Munir Rachman (Jurnal Manajemen, 2022)
This research is motivated by the discipline of the Youth Prima Engineering employees. The aim is to prove the relationship of transformational leadership, interpersonal communication and work discipline in creating their job satisfaction. The sample used was 200 workers from the results of distributing research questionnaires. Then the test is carried out with the instrument test. The explanatory method supports sampling saturated with path analysis techniques. The results of this study found that there was a positive influence of transformational leadership and interpersonal communication on discipline and job satisfaction. The findings of the high work increase of employees have understood good norms, realized and changed pleasant attitudes, resulting in increased job satisfaction. Their willingness to receive information clearly, trusted, and openly, so that the communication that is built can be felt. This relates to the relationship between the work itself and their work discipline. other findings, revealed there was a change in building their job satisfaction. They are aware of and understand the good norms of creating honesty to fulfill the company's goals.